2016
DOI: 10.1371/journal.pone.0152866
|View full text |Cite
|
Sign up to set email alerts
|

Equity in Health Care Financing in Low- and Middle-Income Countries: A Systematic Review of Evidence from Studies Using Benefit and Financing Incidence Analyses

Abstract: IntroductionHealth financing reforms in low- and middle- income countries (LMICs) over the past decades have focused on achieving equity in financing of health care delivery through universal health coverage. Benefit and financing incidence analyses are two analytical methods for comprehensively evaluating how well health systems perform on these objectives. This systematic review assesses progress towards equity in health care financing in LMICs through the use of BIA and FIA.Methods and FindingsKey electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
165
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(177 citation statements)
references
References 41 publications
9
165
0
3
Order By: Relevance
“…The present study suggests that the same clinical sensitivity to comorbid mental disorders and physical pain, in particular arthritis, diabetes, angina, and asthma is essential in the elderly population.Of interest, higher education status and higher income were associated with less pain. The reason for this relationship might be an increased awareness of health risks that might cause pain and less trauma and accidents in higher educated people while those with a better socio-economic status have a better health coverage than those who can't afford it, in particular in LMICs (Asante et al, 2016).…”
Section: General Findingsmentioning
confidence: 99%
“…The present study suggests that the same clinical sensitivity to comorbid mental disorders and physical pain, in particular arthritis, diabetes, angina, and asthma is essential in the elderly population.Of interest, higher education status and higher income were associated with less pain. The reason for this relationship might be an increased awareness of health risks that might cause pain and less trauma and accidents in higher educated people while those with a better socio-economic status have a better health coverage than those who can't afford it, in particular in LMICs (Asante et al, 2016).…”
Section: General Findingsmentioning
confidence: 99%
“…Asante and colleagues [31] point out that in recent years primary health care has benefited mainly the poorest populations, while the hospital services have benefited the better-off in low-and middle-income countries of sub-Saharan Africa, the Asia-Pacific region, Latin America and the Middle East. They concluded that health care financing in LMICs favoured people with better socioeconomic levels even with investments in primary care to increase equity.…”
Section: Discussionmentioning
confidence: 99%
“…-Realizar estudios actuariales, investigación de mercados, y evaluación de planes complementarios por segmentos (9)(10)(11) .…”
Section: Reflexiones Finalesunclassified